Pengaruh Terpaan Iklan Shopee di Televisi Terhadap Minat Beli Remaja di Desa Tariwin - Rahmad Indra Prasetya; R. Ayu Erni Jusnita; Nevrettia Christantyawati; Nurannafi Farni Syam Maella; Zulaikha Zulaikha (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study was conducted by the author with the aim of assessing whether Shopee e-commerce advertisements on television can influence the desire or interest of teenagers in Tariwin Village to make purchases or transactions on the application. This reflects that the more teenagers in Tariwin Village see Shopeeough surveys or questionnaires given to 31 teenagers in Tariwin Village who have seen Shopee advertisements on television, the author found that this study shows that exposure to Shopee advertisements on television can have a significantly positive impact (α = 0.000; t = 5.961). This reflects that the more teenagers in Tariwin Village see Shopee advertisements, the more it increases their interest in making purchases.